Optimization of treatment tactics of combined talus and thoracolumbar spine fractures - Bodnya, Alexander; Sukhin, Uriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The combined injuries of the talus and spine are related to severe injuries. There are differences in the choice of tactics for the treatment of injuries of this localization, the sequence and the necessity for surgical interventions, as well as methods of fixation. Unfavorable results of the treatment encourage the need to optimize of treatment tactics, to revise the terms and stages of surgery. Objective: to determine the treatment tactics and optimal surgical technique in patients with combined injuries of the talus and spine. Methods: retrospective analysis of treatment of 5 men aged from 22 to 35 years, with combined damages of talus bone and thoracolumbar spine was made. The tactics of surgical intervention was based on the early activation of patients through the applying of modern methods of osteosynthesis based on the assessment of the morphology of the injury and the prognosis of functional disorders. At the first stage, the measures included the primary anatomical surgical restoration of the talus with internal fixation, at the second stage — stabilization of spinal fractures with posterior transpedicular fixation. Results: the consequences of combined injuries were studied in terms of 1 to 3 years follow-up. Surgical treatment of talus injuries with differential timely approach allowed us to achieve improvement of anatomical and functional results — (90.5 ± 3.2) points according to AOFAS scale, FFI — (4.8 ± 0.4) points (p ˂ 0.05). The loss of correction of kyphotic deformation was 7.9 ± 0.2°. Oswestry index of pain syndrome did not exceed 20 %, which corresponded to a minimum violation and a good follow-up result that allowed patients to return to their previous physical activity. Conclusions: the tactics of surgical treatment of combined injuries of the talus and thoracolumbar spine requires a differentiated approach in the order and timing of surgical interventions, significantly affects the improvement of functional results in most patients.